Effect of boron deposition and poisoning on the surface exchange properties of LSCF electrode materials of solid oxide fuel cells - Zhao, L.; Hyodo, J.; Chen, Kongfa; Ai, Na; Amarasinghe, S.; Ishihara, T.; Jiang, San Ping (The Electrochemical Society, Inc, 2013)
The relationship between the surface segregation, boron poisoning and surface exchange coefficients of La0.6Sr0.4Co0.2Fe0.8O3−δ, (LSCF) cathodes of solid oxide fuel cells (SOFCs) is studied on dense bar samples using SEM, SIMS and conductivity relaxation method. The SEM results clearly indicate that the segregation on the LSCF surface occurs after heat-treatment at 700–800°C for 48 h, forming isolated particles on the LSCF surface. The presence of volatile boron species accelerates grain growth of the segregated particles and reacts with LSCF. The depth of boron reaction layer after heat-treatment in the presence of E-glass at 700°C, 750°C and 800°C for 48 h was 2, 5 and 40 nm, respectively. The depth profiles analysis of SIMS indicates that there is segregation and enrichment of constituent elements of LSCF on the electrode surface, in line with the depth profile of boron species on the LSCF sample surface layer. Boron deposition and poisoning deteriorates the surface exchange and diffusion processes for the oxygen reduction reaction on LSCF. After exposed to boron at 800°C for 48 h, the surface exchange coefficient, Kchem is 6.0 × 10−5 cm s−1, more than one magnitude lower than 1.1 × 10−3 cm s−1 of as-prepared LSCF samples.